Preparation method of catalyst for liquid-phase one-step oxidation synthesis of methylal from methanol
Through the preparation method of nitrogen-doped activated carbon-supported copper catalyst, the problems of high cost, high energy consumption and high toxicity in the existing methylacetal production process are solved, and high efficiency of one-step oxidation of methanol liquid phase is achieved, with good catalytic activity and environmental protection performance.
Patent Information
- Application Number
- CN202510279221.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-11
AI Technical Summary
The existing methylacetal production process has problems such as high cost, high energy consumption, and equipment corrosion. The vanadium and molybdenum trioxide are highly toxic and do not meet the needs of green production.
The preparation method of nitrogen-doped activated carbon supported copper catalyst is prepared by grinding activated carbon with uniform urea, calcining, washing and drying under a nitrogen atmosphere, and adding copper salts using an equal volume impregnation method to prepare a catalyst for the synthesis of methylacetal in one-step oxidation of methanol liquid phase.
The nitrogen-containing groups are introduced through nitrogen-doped activated carbon surface to promote the reduction of copper particle size and improve dispersion, enhance the interaction force between the active component and the support, inhibit the oxidation and agglomeration of copper, and improve the activity of the catalyst, reaching a methanol conversion rate of 19.1% and a 79.4% methylacetal selectivity.
Smart Images

Figure CN119771477A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of methylal, and in particular to a method for preparing a catalyst for synthesizing methylal by one-step oxidation of methanol in liquid phase. Background Art
[0002] Dimethoxymethane (DMM), also known as dimethoxymethane, is one of the downstream products of methanol. It has the characteristics of low toxicity, good solubility, low boiling point, and fast volatilization. It is widely used in the fields of chemical industry, medicine, cosmetics, etc. In particular, DMM can also be used as a raw material to synthesize the diesel additive DMMn with great application prospects. As a diesel additive, DMMn has a high oxygen content, a high cetane number, and physical properties similar to diesel, which can significantly inhibit the emission of NOx and PM during combustion. Therefore, the development of methylal catalysts and processes has attracted much attention from researchers.
[0003] The traditional production process of methylal is the alcohol-aldehyde condensation method. First, methanol is selectively oxidized to formaldehyde using a catalyst; then the generated formaldehyde and methanol are reacted with an acid catalyst to generate methylal. This process has problems such as high cost, high energy consumption, and equipment corrosion. The one-step synthesis of methylal by the reaction of methanol with oxygen has received great attention in recent years due to its simple process.
[0004] Researchers systematically investigated the effects of different modification methods on the catalytic performance of V-based catalysts and achieved good results, but vanadium is highly toxic and not conducive to environmental protection. Some researchers also used molybdenum as an active component for the one-step oxidation of methanol to synthesize methylal, which has good activity and high selectivity for methylal, but the catalyst preparation process is relatively complicated, and molybdenum trioxide is highly toxic, which does not meet the needs of green production. Copper-based catalysts are a more ideal catalyst for synthesizing methylal, with good low-temperature activity and high selectivity for methylal, but the presence of halogen elements will cause corrosion to stainless steel equipment and even lead to a decrease in catalytic activity. Summary of the invention
[0005] In order to solve the above technical problems, an embodiment of the present invention provides a method for preparing a catalyst for synthesizing methylal by one-step liquid-phase oxidation of methanol.
[0006] To achieve the above object, the embodiments of the present invention adopt the following technical solutions: The present invention provides a method for preparing a catalyst for synthesizing methylal by one-step oxidation of methanol in liquid phase, comprising the following steps: S101, grinding and mixing the activated carbon and urea uniformly for standby use; S102, under a nitrogen atmosphere, calcining, washing and drying the activated carbon and urea ground in S101 for later use; S103, dissolving copper salt in distilled water, and adding the dried product of S102 to prepare nitrogen-doped activated carbon-supported copper catalyst by an equal volume impregnation method; S104. Drying and calcining the nitrogen-doped activated carbon-supported copper catalyst obtained in S103 to obtain a catalyst for the one-step liquid-phase oxidation of methanol to methylal.
[0007] In some embodiments, in S101, the mass ratio of the urea to the activated carbon is (0.5~4):1.
[0008] In some embodiments, in S102, the calcination temperature is 800°C, the calcination time is 10 min, and the heating rate is 10°C / min.
[0009] In some embodiments, in S102, the washing is performed to a pH of 7.
[0010] In some embodiments, in S102, the drying temperature is 100°C.
[0011] In some embodiments, in S103, the copper salt is copper nitrate trihydrate.
[0012] In some embodiments, in S103, the copper loading in the nitrogen-doped activated carbon-supported copper catalyst is 1-15 wt%.
[0013] In some embodiments, in S104, the drying temperature is 100°C.
[0014] In some embodiments, in S104, the calcination temperature is 200°C, the calcination time is 4 hours, and the heating rate is 5°C / min.
[0015] Compared with the prior art, the beneficial effect of the present invention is that nitrogen-containing groups such as pyridinic nitrogen, pyrrolic nitrogen and oxidized pyridinic nitrogen are introduced into the surface of activated carbon by nitrogen doping, wherein the introduction of pyridinic nitrogen can effectively promote the reduction of copper particle size and improve its dispersibility, and at the same time can enhance the interaction between the active component and the carrier, inhibit copper oxidation and agglomeration, and improve the activity of the catalyst. When the urea / activated carbon mass ratio is 2, the pyridinic nitrogen ratio is the largest, the copper particle size is the smallest, the corresponding catalyst has the best catalytic activity, the methanol conversion rate is 19.1%, and the methylal selectivity is 79.4%. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is the XPS spectra of N1s of Examples 1 to 5; Figure 2 is the catalyst particle size distribution diagram of Example 1; Figure 3 is the catalyst particle size distribution diagram of Example 2; Figure 4 is the catalyst particle size distribution diagram of Example 3; Figure 5 is the catalyst particle size distribution diagram of Example 4; Figure 6 This is the catalyst particle size distribution diagram of Example 5. DETAILED DESCRIPTION
[0017] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.
[0018] Implementation 1 S101, urea and activated carbon are mixed in a mass ratio of 0.5:1, and then fully ground; S102, transfer the sample to a quartz boat, and calcine it in a tube furnace at 800°C for 10 min under a nitrogen atmosphere, with a heating rate of 10°C / min; S103, after calcination, the sample was repeatedly washed with distilled water until pH = 7, and then the sample was placed in a common oven at 100 ° C and dried overnight; S104, Cu(NO 3 ) 2 ·3H 2 O was added into distilled water, and then the dried sample in S103 was added, and a catalyst with a copper loading of 5 wt% was prepared by an equal volume impregnation method; The catalysts of S105 and S104 were placed in a common oven and dried at 100°C overnight. Finally, the dried samples were placed in a muffle furnace and calcined at 200°C for 4 h in an air atmosphere with a heating rate of 5°C / min. The corresponding catalysts were obtained and recorded as 5%Cu / N-AC(0.5).
[0019] Implementation 2 S101, urea and activated carbon are mixed in a mass ratio of 1:1, and then fully ground; S102, transfer the sample to a quartz boat, and calcine it in a tube furnace at 800°C for 10 min under a nitrogen atmosphere, with a heating rate of 10°C / min; S103, after calcination, the sample was repeatedly washed with distilled water until pH = 7, and then the sample was placed in a common oven at 100 ° C and dried overnight; S104, Cu(NO 3 ) 2 ·3H 2O was added into distilled water, and then the dried sample in S103 was added, and a catalyst with a copper loading of 5 wt% was prepared by an equal volume impregnation method; The catalysts of S105 and S104 were placed in a common oven and dried at 100°C overnight. Finally, the dried samples were placed in a muffle furnace and calcined at 200°C for 4 h in an air atmosphere with a heating rate of 5°C / min. The corresponding catalysts were obtained and recorded as 5%Cu / N-AC(1).
[0020] Implementation 3 S101, urea and activated carbon are mixed in a mass ratio of 2:1, and then fully ground; S102, transfer the sample to a quartz boat, and calcine it in a tube furnace at 800°C for 10 min under a nitrogen atmosphere, with a heating rate of 10°C / min; S103, after calcination, the sample was repeatedly washed with distilled water until pH = 7, and then the sample was placed in a common oven at 100 ° C and dried overnight; S104, Cu(NO 3 ) 2 ·3H 2 O was added into distilled water, and then the dried sample in S103 was added, and a catalyst with a copper loading of 5 wt% was prepared by an equal volume impregnation method; The catalysts of S105 and S104 were placed in a common oven and dried at 100°C overnight. Finally, the dried samples were placed in a muffle furnace and calcined at 200°C for 4 h in an air atmosphere with a heating rate of 5°C / min. The corresponding catalysts were obtained and recorded as 5%Cu / N-AC(2).
[0021] Implementation 4 S101, urea and activated carbon are mixed in a mass ratio of 3:1, and then fully ground; S102, transfer the sample to a quartz boat, and calcine it in a tube furnace at 800°C for 10 min under a nitrogen atmosphere, with a heating rate of 10°C / min; S103, after calcination, the sample was repeatedly washed with distilled water until pH = 7, and then the sample was placed in a common oven at 100 ° C and dried overnight; S104, Cu(NO 3 ) 2 ·3H 2 O was added into distilled water, and then the dried sample in S103 was added, and a catalyst with a copper loading of 5 wt% was prepared by an equal volume impregnation method; The catalysts of S105 and S104 were placed in a common oven and dried at 100°C overnight. Finally, the dried samples were placed in a muffle furnace and calcined at 200°C for 4 h in an air atmosphere with a heating rate of 5°C / min. The corresponding catalysts were obtained and recorded as 5%Cu / N-AC(3).
[0022] Implementation 5 S101, urea and activated carbon are mixed in a mass ratio of 4:1, and then fully ground; S102, transfer the sample to a quartz boat, and calcine it in a tube furnace at 800°C for 10 min under a nitrogen atmosphere, with a heating rate of 10°C / min; S103, after calcination, the sample was repeatedly washed with distilled water until pH = 7, and then the sample was placed in a common oven at 100 ° C and dried overnight; S104, Cu(NO 3 ) 2 ·3H 2 O was added into distilled water, and then the dried sample in S103 was added, and a catalyst with a copper loading of 5 wt% was prepared by an equal volume impregnation method; The catalysts of S105 and S104 were placed in a common oven and dried at 100°C overnight. Finally, the dried samples were placed in a muffle furnace and calcined at 200°C for 4 h in an air atmosphere with a heating rate of 5°C / min. The corresponding catalysts were obtained and recorded as 5%Cu / N-AC(4).
[0023] Implementation List 6 S101, urea and activated carbon are mixed in a mass ratio of 2:1, and then fully ground; S102, transfer the sample to a quartz boat, and calcine it in a tube furnace at 800°C for 10 min under a nitrogen atmosphere, with a heating rate of 10°C / min; S103, after calcination, the sample was repeatedly washed with distilled water until pH = 7, and then the sample was placed in a common oven at 100 ° C and dried overnight; S104, Cu(NO 3 ) 2 ·3H 2 O was added into distilled water, and then the dried sample in S103 was added, and a catalyst with a copper loading of 1 wt% was prepared by an equal volume impregnation method; The catalysts of S105 and S104 were placed in a common oven and dried at 100°C overnight. Finally, the dried samples were placed in a muffle furnace and calcined at 200°C for 4 h in an air atmosphere with a heating rate of 5°C / min. The corresponding catalysts were obtained and recorded as 1%Cu / N-AC(2).
[0024] Implementation List 7 S101, urea and activated carbon are mixed in a mass ratio of 2:1, and then fully ground; S102, transfer the sample to a quartz boat, and calcine it in a tube furnace at 800°C for 10 min under a nitrogen atmosphere, with a heating rate of 10°C / min; S103, after calcination, the sample was repeatedly washed with distilled water until pH = 7, and then the sample was placed in a common oven at 100 ° C and dried overnight; S104, Cu(NO 3 ) 2 ·3H 2 O was added into distilled water, and then the dried sample in S103 was added, and a catalyst with a copper loading of 10 wt% was prepared by an equal volume impregnation method; The catalysts of S105 and S104 were placed in a common oven and dried at 100°C overnight. Finally, the dried samples were placed in a muffle furnace and calcined at 200°C for 4 h in an air atmosphere with a heating rate of 5°C / min. The corresponding catalysts were obtained and recorded as 10%Cu / N-AC(2).
[0025] Implementation 8 S101, urea and activated carbon are mixed in a mass ratio of 2:1, and then fully ground; S102, transfer the sample to a quartz boat, and calcine it in a tube furnace at 800°C for 10 min under a nitrogen atmosphere, with a heating rate of 10°C / min; S103, after calcination, the sample was repeatedly washed with distilled water until pH = 7, and then the sample was placed in a common oven at 100 ° C and dried overnight; S104, Cu(NO 3 ) 2 ·3H 2 O was added into distilled water, and then the dried sample in S103 was added, and a catalyst with a copper loading of 15 wt% was prepared by an equal volume impregnation method; The catalysts of S105 and S104 were placed in a common oven and dried at 100°C overnight. Finally, the dried samples were placed in a muffle furnace and calcined at 200°C for 4 h in an air atmosphere with a heating rate of 5°C / min. The corresponding catalysts were obtained and recorded as 15%Cu / N-AC(2).
[0026] Comparative Example 1 S101, fully grind 1.980 g of activated carbon; S102, transfer the sample to a quartz boat, and calcine it in a tube furnace at 800°C for 10 min under a nitrogen atmosphere, with a heating rate of 10°C / min; S103, after calcination, the sample was repeatedly washed with distilled water until pH = 7, and then the sample was placed in a common oven at 100 ° C and dried overnight; S104, 0.076g Cu(NO 3 ) 2 ·3H 2 O was added to 3.015 g of distilled water, and a catalyst with a loading of 5 wt% was prepared by an equal volume impregnation method; The catalysts of S105 and S104 were placed in a common oven and dried at 100°C overnight. Finally, the dried samples were placed in a muffle furnace and calcined at 200°C for 4 h in an air atmosphere with a heating rate of 5°C / min. The corresponding catalysts were obtained and recorded as 5%Cu / AC.
[0027] The catalysts prepared in Examples 1 to 5 were tested in a 100 mL autoclave for the catalytic activity of methanol in the one-step oxidation reaction of methanol to methylal. 15 mL of methanol and 0.6 g of catalyst were added to the autoclave, and 3 MPa of O was charged at room temperature. 2 The reaction was carried out at 300 rpm and 140°C for 4 h, then cooled to room temperature and the product composition was analyzed by gas chromatography. The methanol conversion rate and the selectivity of the target product methylal and the by-product methyl formate (MF) are shown in Table 1.
[0028] Table 1 Catalytic performance of catalysts in one-step oxidation of methanol to methylal in liquid phase
[0029] As can be seen from Table 1, when the urea specific gravity is less than 2 times, as the urea specific gravity increases, the methanol conversion rate gradually increases. When the urea specific gravity is 2 times, the methanol conversion rate reaches the maximum, which is 19.1%. When the urea specific gravity further increases, the methanol conversion rate decreases accordingly. When the urea specific gravity is 4 times, the methanol conversion rate decreases to 15.1%.
[0030] Reaction conditions: m(5%Cu / N-AC(X))=0.6 g, V(CH 3 OH)=15 ml,P(O 2 )= 3.0MPa, T= 140℃, t= 4h, Note: S stands for selectivity, DMM stands for methylal, and MF stands for methyl formate.
[0031] pass Figure 1 The XPS spectrum fitting results of N1s of 5%Cu / N-AC(X) with different urea specific gravity are shown in Table 2 below.
[0032] Table 2
[0033] Depend on Figure 1It can be seen from the XPS peak fitting results in Table 2 that nitrogen doping introduces nitrogen-containing groups such as pyridinic nitrogen, pyrrolic nitrogen and oxidized pyridinic nitrogen to the surface of activated carbon. The introduction of pyridinic nitrogen can effectively promote the reduction of copper particle size and improve its dispersibility. At the same time, it can also enhance the interaction between the active component and the carrier, inhibit copper oxidation and agglomeration, and improve the activity of the catalyst. When the urea / activated carbon mass ratio is 2, the pyridinic nitrogen ratio is the largest, and the copper particle size is the smallest (such as Figure 4 The corresponding catalyst has the best catalytic activity, with a methanol conversion rate of 19.1% and a methylal selectivity of 79.4%.
[0034] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.
[0035] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a catalyst for synthesizing methylal by one-step oxidation of methanol in liquid phase, characterized in that: The following steps are involved: S101, grinding and mixing the activated carbon and urea uniformly for standby use; S102, under a nitrogen atmosphere, calcining, washing and drying the activated carbon and urea ground in S101 for later use; S103, dissolving copper salt in distilled water, and adding the dried product of S102 to prepare nitrogen-doped activated carbon-supported copper catalyst by an equal volume impregnation method; S104. Drying and calcining the nitrogen-doped activated carbon-supported copper catalyst obtained in S103 to obtain a catalyst for the one-step liquid-phase oxidation of methanol to methylal.
2. The preparation method according to claim 1, characterized in that: In S101, the mass ratio of the urea to the activated carbon is (0.5-4):
1.
3. The preparation method according to claim 1, characterized in that: In S102, the calcination temperature is 800°C, the calcination time is 10 min, and the heating rate is 10°C / min.
4. The preparation method according to claim 1, characterized in that: In S102, the washing is performed until the pH value reaches 7.
5. The preparation method according to claim 1, characterized in that: In S102, the drying temperature is 100°C.
6. The preparation method according to claim 1, characterized in that: In S103, the copper salt is copper nitrate trihydrate.
7. The preparation method according to claim 1, characterized in that: In S103, the copper loading amount of the nitrogen-doped activated carbon-supported copper catalyst is 1-15 wt%.
8. The preparation method according to claim 1, characterized in that: In S104, the drying temperature is 100°C.
9. The preparation method according to claim 1, characterized in that: In S104, the calcination temperature is 200°C, the calcination time is 4 hours, and the heating rate is 5°C / min.
Citation Information
Patent Citations
Method for synthesizing methylal by means of direct oxidation of methanol
CN107021877A
Copper-based catalyst taking nitrogen-modified activated carbon as carrier as well as preparation method and application thereof
CN111420694A
Application of metal nanocluster catalyst in one-step preparation of acetal from alcohol
CN112973681A
Method for synthesizing dimethoxymethane through selective hydrogenation of carbon dioxide
CN114349607A
Preparation of nitrogen modified catalyst and application of nitrogen modified catalyst in preparation of cyclohexanone through phenol hydrogenation
CN114602524A